2015
DOI: 10.1016/j.desal.2014.12.038
|View full text |Cite
|
Sign up to set email alerts
|

Energy consumption in desalinating produced water from shale oil and gas extraction

Abstract: On-site treatment and reuse is an increasingly preferred option for produced water management in unconventional oil and gas extraction. This paper analyzes and compares the energetics of several desalination technologies at the high salinities and diverse compositions commonly encountered in produced water from shale formations to guide technology selection and to inform further system development. Produced water properties are modeled using Pitzer's equations, and emphasis is placed on how these properties dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
145
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 209 publications
(152 citation statements)
references
References 58 publications
5
145
0
Order By: Relevance
“…Conventional spiral wound reverse osmosis (RO), the workhorse of the desalination industry today, is typically operated below 70 bar of applied pressure [1]. As a result, RO is not directly applicable to desalination of these saltier streams for which the osmotic pressure can be as high as 300 bar [2].…”
Section: Context: Desalination Up To High Salinitymentioning
confidence: 99%
See 1 more Smart Citation
“…Conventional spiral wound reverse osmosis (RO), the workhorse of the desalination industry today, is typically operated below 70 bar of applied pressure [1]. As a result, RO is not directly applicable to desalination of these saltier streams for which the osmotic pressure can be as high as 300 bar [2].…”
Section: Context: Desalination Up To High Salinitymentioning
confidence: 99%
“…At higher salinity levels, a peak value of GOR was observed with changing in feed inlet flow rate. Similarly, Thiel et al [2] used numerical models of PGMD to illustrate the existence of an optimal system size (represented through a terminal temperature difference) at which GOR is maximized when the feed inlet flow rate is held constant.…”
Section: Large Area Systems Measuring Gor and Fluxmentioning
confidence: 99%
“…Osmotically driven processes such as Pressure Retarded Osmosis (PRO) and the more recently introduced Assisted Forward Osmosis (AFO) may experience pressures above 4.7 MPa [10,11] and 0.6 MPa 7 respectively [12]. Unconventional reverse osmosis configurations have also recently been investigated for treating oil and gas produced water to salinities near saturation values of 260 g/kg and pressures near 30 MPa [13]. For accurately modeling conventional and unconventional desalination technologies, there is a need for accurate prediction of the thermophysical properties of seawater at elevated pressures and salinities.…”
Section: Been Made By the International Association For The Propertiementioning
confidence: 99%
“…Under reversible conditions, the work required would be the 'least work' thermodynamically possible, which for brine concentration and crystallization we designate asẆ least bc andẆ least crys , respectively. Thus, the least work for brine concentration is the least work for concentrating from a given feed salinity up to saturation, while the least work for crystallization is the least work for taking a saturated solution up to complete separation of water and salt [30].…”
Section: Salt Production and Zero-discharge Desalinationmentioning
confidence: 99%
“…The activity coefficients were obtained from an implementation by Thiel et al [30,33] of Pitzer's equations modeling the thermodynamics of aqueous electrolyte solutions [34][35][36][37][38][39]. Thiel et al [30] found that aqueous NaCl serves as a reasonable surrogate for the property estimation in certain high salinity waters.…”
Section: Salt Production and Zero-discharge Desalinationmentioning
confidence: 99%